2020
DOI: 10.1007/s00330-020-06691-2
|View full text |Cite
|
Sign up to set email alerts
|

Lumbosacral transitional vertebrae are associated with lumbar degeneration: retrospective evaluation of 3855 consecutive abdominal CT scans

Abstract: Objectives To assess the prevalence of lumbosacral transitional vertebra (LSTV) and associated spinal degenerative changes on abdominal CT scans in Caucasian population. Material and methods A total of 3855 abdominal CT scans of the year 2017 from a single hospital were retrospectively assessed for LSTV, disc degeneration (DD), and facet joint degeneration (FD). An age-and sex-matched 150-subject control group without LSTV was picked at random. Multivariable logistic regression was used for the analysis. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 31 publications
2
24
0
1
Order By: Relevance
“…The prevalence of LSTV in the literature is reported between 4% and 37%. The systematic evaluation of some studies conducted between 2000 and 2020 found a mean LSTV prevalence of 19.4% [6][7][8][9][10][11][12][13][14][15][16][17][18]. LSTV was detected in 18.3% of 972 cases in our study.…”
Section: Discussionmentioning
confidence: 51%
“…The prevalence of LSTV in the literature is reported between 4% and 37%. The systematic evaluation of some studies conducted between 2000 and 2020 found a mean LSTV prevalence of 19.4% [6][7][8][9][10][11][12][13][14][15][16][17][18]. LSTV was detected in 18.3% of 972 cases in our study.…”
Section: Discussionmentioning
confidence: 51%
“…Spines with <> 5 lumbar vertebrae are uncommon (71) . Transitional vertebrae may be more common (72) , but it is unclear whether this would consistently compromise labeling from a lateral spine x-ray. The assumption is that the vertebrae were correctly labeled in the majority of cases and the possibility of mislabeled vertebrae in a minority of cases would not significantly affect the results.…”
Section: Resultsmentioning
confidence: 99%
“…The two musculoskeletal radiologists identified 45 (33%) hips with lumbosacral transitional vertebrae, which were classified according to the Castellvi type classification [ 34 ]. Castellvi type 3B with bilateral fusion of the transverse process and sacrum was the most frequently identified variant determined by both readers, followed by 2A [ 16 ].…”
Section: Resultsmentioning
confidence: 99%